Exploring the Role of Motivation in Shaping University Students’ Academic Engagement - Vieryal Afrilia; Geminastiti Sakkir; Fitri Radhiyani (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2026)
Motivation plays a vital role in shaping students’ learning engagement and academic success in higher education. This study explores the factors influencing motivation among students in the English Language Education Study Program at Universitas Negeri Makassar (UNM). Using Self-Determination Theory (SDT) and Achievement Goal Theory (AGT) as frameworks, a qualitative case study was conducted through semi-structured interviews with selected participants. The findings show that motivation is influenced by both intrinsic factors, such as personal interest and the desire for mastery, and extrinsic factors, including grades, recognition, and career aspirations. Peer support and lecturer teaching approaches also emerged as significant contributors to students’ motivation. These results highlight the need for educators to foster supportive learning environments that strengthen students’ motivation and engagement.